Quando si dice non più. Ragionando sugli artt. 5, comma, 1 e 6, commi 1 e 3 della Legge n. 40/2004 (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Reasoning on articles 5, paragraph 1, and 6, paragraphs 1 and 3, of law no. 40 of 2004, the essay wonders what is the most "fair" definition of judgments against the male partner of a couple who, after having given their consent to the use of MAP techniques, before such treatment is completed by means of the implantation in utero of the embryos formed, manifest the firm will not to continue in the couple's bond, dissolving it, and the equally strenuous choice to interrupt the search for the child, revoking the consent originally expressed for the use of new procreative methods.
Keywords: Informed consent; withdrawal of consent; freedom not to procreate; principle of self-determination; paternity